Influence of water treatment on digestion dynamics of steers consuming high- and low-forage diets - Harmon, D.L.; Flood, A.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The influence of drinking water treatment (Oxion Inc., Hugoton, KS) on digestion and metabolism was evaluated in steers fed low- and high-forage diets. Water treatment did not influence digestibility of any nutrient measured nor did it influence the profile of ruminal metabolites. Water treatment did increase water consumption two- to threefold and also increased ruminal fractional water outflow (%/h) for steers fed the high forage, but not the high concentrate, diet. Increased water consumption could be a beneficial response, but it is not known if water consumption increases with management programs different than those used in the present study.
Keywords: Beef; Steer; Water; Digestibility; Intake; Rumen